Medieval urban landscape in northeastern Mesopotamia - Nováček, Karel, (Archaeopress archaeology., 2016)
The authors investigate the sites which formed an urban network from 6th to 19th centuries in the region of northeastern Mesopotamia, bounded by the rivers Great Zab, Little Zab and Tigris.